An investigation into some critical computer networking parameters : Internet addressing and routing - Isted, Edwin David (Rhodes University, Faculty of Science, Department of Computer Science, 1996)
This thesis describes the evaluation of several proposals suggested as replacements for the currenT Internet's TCPJIP protocol suite. The emphasis of this thesis is on how the proposals solve the current routing and addressing problems associated with the Internet. The addressing problem is found to be related to address space depletion, and the routing problem related to excessive routing costs. The evaluation is performed based on criteria selected for their applicability as future Internet design criteria. AIl the protocols are evaluated using the above-mentioned criteria. It is concluded that the most suitable addressing mechanism is an expandable multi-level format, with a logical separation of location and host identification information. Similarly, the most suitable network representation technique is found to be an unrestricted hierarchical structure which uses a suitable abstraction mechanism. It is further found that these two solutions could adequately solve the existing addressing and routing problems and allow substantial growth of the Internet.
Keywords: Computer networks; Internet; Electronic mail systems